2020
DOI: 10.1155/2020/1976298
|View full text |Cite
|
Sign up to set email alerts
|

Withania frutescens. L Extract: Phytochemical Characterization and Acute and Repeated Dose 28-Day Oral Toxicity Studies in Mice

Abstract: Background. Withania frutescens. L (W. frutescens) is a perennial woody medicinal plant belonging to family Solanaceae largely used by the indigenous population to Morocco for the treatment of disease. Objective. The purpose of this study was to investigate the chemical composition, acute, and subacute toxicity of W. frutescens extract in mice. Materials and Methods. The phytochemical composition of W. frutescens extract was determined using a gas chromatograph (GC/MS). Acute toxicity study was carried out in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…For the other compounds, 3.18 ± 74% and 4.22 ± 0.36% were detected by both columns, respectively. therefore, the studied plant was considered safe in animals treated under both acute and subacute toxicity conditions [22][23][24]. Preliminary phytochemical screening of W. frutescens extracts showed the presence of some compound classes including tannins, coumarins, saponins, and mucilage [25].…”
Section: Phytochemical Composition Of Essential Oilmentioning
confidence: 98%
See 1 more Smart Citation
“…For the other compounds, 3.18 ± 74% and 4.22 ± 0.36% were detected by both columns, respectively. therefore, the studied plant was considered safe in animals treated under both acute and subacute toxicity conditions [22][23][24]. Preliminary phytochemical screening of W. frutescens extracts showed the presence of some compound classes including tannins, coumarins, saponins, and mucilage [25].…”
Section: Phytochemical Composition Of Essential Oilmentioning
confidence: 98%
“…Moreover, the chemical analysis of the W. frutescens.L extract showed that this plant possessed pentacarbonyl (13.22%), 2-phenazine carbonitrile (10.64%), Terpinenol-4 (10.04%), 4H-1-benzopyran-4-one,2,3-dihydro-5,7-dihydroxy-2phenyl(S) (8.76%), and bicyclo [3.1.1]heptane, 6,6-dimethyl-2-methylene (28.48%) [20,21]. Earlier works showed no toxic effects in animals treated with the W. frutescens extract, therefore, the studied plant was considered safe in animals treated under both acute and subacute toxicity conditions [22][23][24]. Preliminary phytochemical screening of W. frutescens extracts showed the presence of some compound classes including tannins, coumarins, saponins, and mucilage [25].…”
Section: Introductionmentioning
confidence: 95%
“…The furnace temperature program was set to 70-270 • C at 4 • C/min and then maintained at 270 • C for 20 min. The temperature of the injector was set to 280 • C and that of the detector to 290 • C. The injection was carried out in fractionated mode (El Moussaoui et al, 2020).…”
Section: Identification Of Phytochemical Compoundsmentioning
confidence: 99%
“…The continued use of herbal medicines in traditional medicine is attributable not only to cultural and poverty reasons but also to its effectiveness against many diseases as they possess the ability to synthesize, through complex metabolic pathways, many bioactive compounds at different biological and pharmacological properties [ 1 , 2 ]. So, in a quarter of biomedical medications regularly prescribed, at least one active ingredient comes from these plants and the rest of the substances are chemically produced in laboratories [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…So, in a quarter of biomedical medications regularly prescribed, at least one active ingredient comes from these plants and the rest of the substances are chemically produced in laboratories [ 3 ]. Therefore, the traditional herbal medicines are getting more and more significant attention in global population and the search for new natural drugs with fewer side effects, bringing an additional change in the modern world, is then highly appreciated [ 2 , 4 ]. However, continued use of these plants for medication without validly reporting on their toxic profiles scientifically could negatively affect human health [ 2 ].…”
Section: Introductionmentioning
confidence: 99%